A case of bovine nasal schistosomiasis - Saharee, Abdul Aziz; Abdullah Sani, Rehana; Sheikh Omar, Abdul Rahman; Greer, G. J. (Persatuan Doktor Veterinar Malaysia, 1984)
A case of bovine nasal schistosomiasis is reported. Clinically the animal had loud respiration, tachypnoea, bilateral serous nasal discharge and numerous raised nodules in the anterior nasal mucosa. Histological section showed an infiltration of eosinophils, lymphocytes, plasma cells, macrophages, fibroblasts and a [ewLanghan -s giant cells in the lamina propria of the nasal mucosa, Ovoid structures resembling schistosoma eggs were also seen amidst these cells, Numerous boomerang-shaped eggs were seen in the digested tissue biopsy sample